2020
DOI: 10.1038/s41419-020-03160-y
|View full text |Cite
|
Sign up to set email alerts
|

circ-CBFB upregulates p66Shc to perturb mitochondrial dynamics in APAP-induced liver injury

Abstract: p66Shc, a master regulator of mitochondrial reactive oxygen species (mtROS), is a crucial mediator of hepatocyte oxidative stress. However, its functional contribution to acetaminophen (APAP)-induced liver injury and the mechanism by which it is modulated remain unknown. Here, we aimed to assess the effect of p66Shc on APAP-induced liver injury and to evaluate if circular RNA (circRNA) functions as a competitive endogenous RNA (ceRNA) to mediate p66Shc in APAP-induced liver injury. p66Shc-, miR-185-5p-, and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Another example can be the 66 kDa isoform of Shc (p66shc), an adaptor and redox protein that has been already linked to the lipid metabolism regulation by numerous reports 192 . It has been demonstrated that p66Shc participates in various mechanisms of liver injury 193,194 . In livers of NAFLD patients, expression levels of apoptosis regulating proteins p53, p21 and p66Shc were significantly increased 195 .…”
Section: Ros and Rns Culprits Or Bystanders Of Nafld Progressionmentioning
confidence: 99%
“…Another example can be the 66 kDa isoform of Shc (p66shc), an adaptor and redox protein that has been already linked to the lipid metabolism regulation by numerous reports 192 . It has been demonstrated that p66Shc participates in various mechanisms of liver injury 193,194 . In livers of NAFLD patients, expression levels of apoptosis regulating proteins p53, p21 and p66Shc were significantly increased 195 .…”
Section: Ros and Rns Culprits Or Bystanders Of Nafld Progressionmentioning
confidence: 99%
“…Previous studies have found that it works by triggering perturbations in mitochondrial dynamics. circ-CBFB acts as a ceRNA to play a regulatory role during cell injury, which may provide a potential therapeutic target [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…For acetaminophen (APAP)-induced liver injury, p66Shc, a master regulator of mtROS, is upregulated in liver tissues in response to APAP. circ-CBFB acts as the sponge of miR-185-5p, triggering mitochondrial dynamics perturbation via p66Shc [95]. For the hydrogen peroxide (H 2 O 2 )induced injury, circRNA-4099 augments H 2 O 2 -induced damage by inhibiting miR-706 and triggering Keap1/Nrf2 and p38MAPK in the L02 cells [96].…”
Section: Liver Injury and Liver Regenerationmentioning
confidence: 99%